Antihypertensive Effects of Fig Leaves (Ficus carica L.) Ethanolic Extract: An In Vitro and In Silico Study - Muhammad Fariez Kurniawan; Suci Apriliyanti (Jurnal Farmasi Sains dan Komunitas (Journal of Pharmaceutical Sciences and Community), 2025)
Pathological conditions of hypertension can occur due to contractions of blood vessels. Vascular contraction response occurs when epinephrine successfully binds to adrenergic receptors. Objective: This study aims to determine the antagonistic activity of giving ethanolic extracts of fig leaves (Ficus carica L. Folium) in β-adrenergic receptors of isolated aortic organs and to determine the value of the affinity of one of the compounds present in fig leaf extract, which has a strong potential as a vasodilator agent to treat hypertension. This study uses in silico and in vitro methods. The in silico method test used molecular docking, and the in vitro method test used an organ bath on a guinea pig's aortic organs. An in silico docking test was conducted on compounds suspected to have a vasodilator effect, namely Quercetin and β-adrenergic receptor test with native ligand timolol (PDB ID: 6PS6). The in vitro testing of foliar ethanolic extracts was done by administering 0.5 mg of extracts at 100 µL and 200 µL. The resulting data included a percent of aortic contraction data on administering epinephrine concentration series, which was transformed into a pD2 value. The result from the in silico method showed that quercetin binding affinity value (-7.8 kcal/mol) was better than timolol as a comparison (-6.4 kcal/mol). The result from the in vitro method showed that the fig leaf's ethanolic extract could shift the percentage curve of contraction response to the administration of epinephrine series by decreasing the pD2 value. A dose of 0.5 mg volume 200 µL is effective because it gives a significant difference to the control group but does not show a significant difference in the comparison group. Conclusively, the ethanolic extract of fig leaves can be developed as a vasodilator agent.